PENGARUH PERAN ORANG TUA DAN POLA ASUH ORANG TUA TERHADAP HASIL BELAJAR SISWA SDN CIPUTAT - Ghina Nurrahmah; Nana Hendra Cipta; Siti Rokmanah (STKIP Subang, 2023)
This research has a main focus with the aim of determining the influence of parental role variables and parenting patterns on the learning outcomes of Ciputat State Elementary School students. The research was prepared using a quantitative method approach. Conducted using a research sample of 3rd grade students at Ciputat State Elementary School. The research sample was obtained by random sampling. Data was obtained by collecting it using a questionnaire or questionnaire which was prepared using a technique using a Likert scale. The research results were carried out with descriptive tests, normality tests with Kolmogorov Smirnov linearity tests, multicollinearity tests and heteroscedasticity tests. To determine the influence between variables, a multiple regression test was carried out using the t test with a significance level of 0.05. The research results show that the majority of parents are in the very strong parental role category with a percentage of 52.2%, the majority apply democratic and accepting parenting with a percentage of 87.0% and the majority of student learning outcomes are in the very good category 65.2% . The results of the multiple regression t test showed a significance result of 0.000<0.05 on the variable of the role of parents on student learning outcomes, so it can be seen that the role of parents has an influence on student learning outcomes. For the parenting pattern variable, the results obtained at a significance level of 0.001<0.05, so it is also known that parental parenting influences or influences student learning outcomes. Keywords: learning outcome, parenting style, elementary school students